Revisiting Privatisation In Malaysia: The Importance Of Institutional Process - Nambiar, Shankaran (Asian Academy of Management (AAM), 2009)
This paper argues that institutional process are essential to the execution of economic policy. In the absence of adequate institutional processes, well-intentioned economic policies may not be implemented in the manner expected by theory. The case of privatisation in Malaysia is used as an example to illustrate why institutional processes must be put into place in order to achieve the full benefit of economic policies. Economic theory suggests that privatisation, rather than state-ownership of enterprises, leads to greater economic efficiency. However, this is only the case if privatisation initiatives are carried out in a manner that consistent with good institutional practice. This paper suggests that there is a prima facie case for establishing transparent institutions in order to gain from the proper implementation of economic policy.